2020
DOI: 10.5744/bi.2019.1014
|View full text |Cite
|
Sign up to set email alerts
|

“Captain of All These Men of Death”: An Integrated Case Study of Tuberculosis in Nineteenth-Century Otago, New Zealand

Abstract: The South Island of New Zealand saw several major waves of migration in the mid-nineteenth century, predominantly from Europe but also with an ethnically distinct Chinese presence. The rural community of Milton, Otago, was a settler community established primarily by immigrants from the United Kingdom in search of a better quality of life. However, these settlers faced unique challenges related to surviving in an isolated location with very little infrastructure compared to their origin populations. In 2016 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Our findings address the original speculation in Snoddy et al (2020) that the limb function of B21 was restricted to some degree by the one-sided hip pathology. We add further to the biochemical and paleopathological analyses, combined with documented life history, by offering a more direct histological method of testing for individual-level localized bone functional adaptation in contexts of immobilization.…”
Section: Histomorphometry: Implications For the Construction Of Osteo...supporting
confidence: 87%
See 1 more Smart Citation
“…Our findings address the original speculation in Snoddy et al (2020) that the limb function of B21 was restricted to some degree by the one-sided hip pathology. We add further to the biochemical and paleopathological analyses, combined with documented life history, by offering a more direct histological method of testing for individual-level localized bone functional adaptation in contexts of immobilization.…”
Section: Histomorphometry: Implications For the Construction Of Osteo...supporting
confidence: 87%
“…He died on July 5, 1873, and his cause of death is listed as "pneumonic phthisis haemorrhage." It was found that B21 exhibited lesions that, along with his documented cause of death, strongly support a diagnosis of disseminated tuberculosis (Snoddy et al 2020). These include extensive destruction of the trabecular bone in the proximal femur (Fig.…”
Section: Cortical Bone Remodeling and Unilateral Limb Pathologymentioning
confidence: 92%
“… Note : Data compiled from Buckley et al (2020), King, Petchey, et al (2021), Snoddy et al (2020, 2021), and Petchey, Buckley, Hil, et al (2018). Adult age‐at‐death estimates are defined as young adult (20–34 years), mid‐adult (35–49 years), and older adult (50+ years).…”
Section: Methodsmentioning
confidence: 99%
“…Modern historians have proposed that the early immigrant populace of New Zealand experienced better health and longer lifespans than their contemporaries back home (Inwood & Maxwell‐Stewart, 2015; Woodward & Blakely, 2014). This assumption has only recently been critically examined from a bioarcheological perspective (Buckley et al, 2020; King et al, 2022; King, Buckley, et al, 2020, 2021; King, Petchey, et al, 2020, 2021; Petchey, Buckley, Hil, et al, 2018; Petchey, Buckley, & Scott, 2018; Snoddy et al, 2020, 2021), with the Southern Cemeteries Research Project, a joint endeavor between the University of Otago and Southern Archaeology Ltd. Bioarcheological and paleopathological investigations of individuals from the sampled cemetery assemblage indicate that the colonial experience of health is more nuanced than suggested by the historical narrative, with evidence for traumatic injuries (Buckley et al, 2020; Petchey & Buckley, 2022), infectious diseases (Snoddy et al, 2020), high infant mortality (Buckley et al, 2020), and dietary stress (King et al, 2023; King, Buckley, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Over the Victorian period, farming, waterworks and gasworks industries began to boom in Invercargill, further promoting the city's development (Bailey, 1966). Recently, bioarcheological studies of colonial period cemeteries have shed light on the lives of Victorian New Zealanders in a small number of Otago farming and gold mining communities in Lawrence (Gabriel and Ardrossan Street Cemeteries) and Milton (St John's Cemetery) (Buckley et al, 2020; King et al, 2020; King et al, 2022; King, Buckley, et al, 2021; King, Petchey, et al, 2021; Snoddy et al, 2020). However, this is the first bioarcheological investigation of Victorian era people recovered from an urban center in Aotearoa.…”
Section: Introductionmentioning
confidence: 99%